Sovereign Wealth Funds and Long-Term Development Finance : Risks and Opportunities - Gelb, Alan (World Bank, Washington, DC, 2014)
Sovereign wealth funds represent a large and growing pool of savings. An increasing number of these funds are owned by natural resource exporting countries and have a variety of objectives, including intergenerational equity and macroeconomic stabilization. Traditionally, these funds have invested in external assets, especially securities traded in major markets. But the persistent infrastructure financing gap in developing countries has motivated some governments to encourage their sovereign wealth funds to invest domestically. This paper proposes some basic elements of a conceptual framework to create a system of checks and balances to help ensure that the sovereign wealth funds do not undermine macroeconomic management or become a vehicle for politically driven "investments." First, the risks and opportunities of domestic investment by sovereign wealth funds are analyzed. Central issues are the relationship of sovereign wealth fund financing to the budget process and to the procurement systems of sector ministries, as well as the establishment of appropriate benchmarks and safeguards to ensure the integrity of investment decisions. The paper argues that a well-governed sovereign wealth fund, with a sound mandate and professional management and staffing, can possibly improve the quality of the public investment program. But its mandate should not duplicate that of other government institutions with investment mandates, such as the budget, the national development bank, the investment authority, and state-owned enterprises. Establishing rules on the type of investment (for example, commercial and/or quasi-commercial) and its modalities (for example, no controlling stakes, leveraging private investment) is one way to ensure separation between the activities of the sovereign wealth fund and those of other institutions. The critical issue remains that of limiting the sovereign wealth fund's investment scope to that appropriate for a wealth fund. If investments that generate quasi-market returns are permitted, the size of the home bias should be clearly stipulated and these investments should be reported separately.